Foreign language learning through collaborative writing in knowledge building forums - Manegre, Marni; Gutiérrez-Colón, Mar (Interactive learning environments, 2023)
Knowledge building occurs when students work together and participate in idea-centred discussions where they share information and create knowledge collectively. This research explores whether knowledge building in knowledge forums using English as the lingua franca can facilitate in foreign language learning. An analysis was done on how Catalan students in secondary schools worked together on collaborative writing tasks in such forums using appropriate scaffolding to organize their thoughts and facilitate the discussion. The students were participating in the Knowledge Building International Project (KBIP), which is based on the concept that students can learn while working together in computer-assisted learning environments. This study applied methods using data triangulation and method triangulation where the students were observed throughout the knowledge building process, and both qualitative and quantitative data were collected and analysed for evidence of foreign language learning. The quantitative data was collected through a pre-test and a post-test, while the qualitative data was collected through observation and a digital questionnaire. The results show an increase overall in the performance of the foreign language. In particular, the analysis determined that the comprehension of the subject matter and writing abilities in the L2 showed an increase at high confidence levels.